Functional and technical outcomes in acute ischemic stroke patients with hyperdense middle cerebral artery sign treated with endovascular thrombectomy - Chen, Yimin; Diana, Francesco; Mofatteh, Mohammad; Zhou, Sijie; Chen, Juanmei; Huang, Zhou; Wu, Weijuan; Yang, Yajie; Zeng, Zhiyi; Zhang, Weijian; Ouyang, Ziqi; Nguyen, Thanh N.; et al. (Frontiers in Neurology, 2023)
Background and objective The hyperdense middle cerebral artery sign (HMCAS) is observed in a proportion of patients with acute ischemic stroke (AIS). This sign reflects the presence of an intravascular thrombus rich in red blood cells. Several studies have demonstrated that HMCAS increases the risk of poor outcomes in AIS patients treated with IV thrombolysis or no reperfusion therapy; however, whether HMCAS predicts a poor outcome in patients treated with endovascular thrombectomy (EVT) is less clear. We aimed to evaluate the functional outcome by the modified Rankin scale (mRS) at 90 days and technical challenges in patients with HMCAS undergoing EVT. Methods We studied 143 consecutive AIS patients with middle cerebral artery M1 segment or internal carotid artery + M1 occlusions who underwent EVT. Results There were 73 patients (51%) with HMCAS. Patients with HMCAS had a higher frequency of cardioembolic stroke (p = 0.038); otherwise, no other baseline difference was observed. No differences in functional outcomes (mRS) at 90 days (p = 0.698), unfavorable outcomes (mRS > 2) (p = 0.929), frequency of symptomatic intracranial hemorrhage (p = 0.924), and mortality (mRS-6) (p = 0.736) were observed between patients with and without HMCAS. In patients with HMCAS, EVT procedures were 9 min longer, requiring a higher number of passes (p = 0.073); however, optimal recanalization scores (modified thrombolysis in cerebral infarction: 2b-3) were equally achieved by both groups. Conclusion Patients with HMCAS treated with EVT do not have a worse outcome at 3 months compared with no-HMCAS patients. Patients with HMCAS required a greater number of thrombus passes and longer procedure times.